2022
DOI: 10.1007/s11160-022-09744-5
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the phylogenetic and ecological drivers of beak shape variability in cephalopods

Abstract: Cephalopod beaks are essential for prey acquisition and fragmentation during feeding. Thus, it is expected that ecological pressures affect cephalopod beak shape. From a practical perspective, these structures are also used to identify gut contents of marine megafauna, such as toothed whales, sharks, seabirds, and large pelagic fishes. Here, we investigated the relative importance of ecological pressures and phylogenetic relatedness in the evolution of beak shape using a wide range of Mediterranean cephalopod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…However, the phenogram of beak shape in this study could still indicate the classification relationship of cephalopods at the family level, as demonstrated by molecular phylogenetic trees and phylogenetic signal results (Figure , the left side of Figures 5, 6, 9; Tables 3, 4). Previous studies have also suggested a strong relationship between beak shape and phylogeny (Neige & Dommergues, 2002; Roscian et al, 2022; Sánchez‐Márquez et al, 2023; Tanabe et al, 2015). Above all, we found that Lepidoteuthidae and Octopodoteutidae have very different body morphology in adults but similar beaks and are closely phylogenetically related (Fernández‐Álvarez et al, 2022; Jereb & Roper, 2005b; Jereb et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…However, the phenogram of beak shape in this study could still indicate the classification relationship of cephalopods at the family level, as demonstrated by molecular phylogenetic trees and phylogenetic signal results (Figure , the left side of Figures 5, 6, 9; Tables 3, 4). Previous studies have also suggested a strong relationship between beak shape and phylogeny (Neige & Dommergues, 2002; Roscian et al, 2022; Sánchez‐Márquez et al, 2023; Tanabe et al, 2015). Above all, we found that Lepidoteuthidae and Octopodoteutidae have very different body morphology in adults but similar beaks and are closely phylogenetically related (Fernández‐Álvarez et al, 2022; Jereb & Roper, 2005b; Jereb et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
“…The phylogenetic signals of beak shape were assessed by using a phylogenetic tree in combination with geometric morphometric approaches. This assessment is a cutting‐edge approach for studying cephalopods and can be used as an analytical framework (Adams & Collyer, 2018; Baken et al, 2021; Díaz‐Santana‐Iturrios et al, 2022; Roscian et al, 2022; Sánchez‐Márquez et al, 2023). In this study, beak shapes showed a strong phylogenetic signal (K = 1.420 and 0.912 for upper and lower beaks, respectively, p = .001), which is consistent with Sánchez‐Márquez et al (2023), indicating that the information contained in the lateral shape of the beaks is a useful material for cephalopod phylogeny studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the authors would like to thank the veterinary team of the IUSA‐ULPGC for providing the samples for study and the BIOECOMAC research group of the University of La Laguna for their support during the campaign. We are very grateful for the cession of the reference collection of cephalopod beaks AFOC (ICM‐CSIC, Barcelona; Sánchez‐Márquez et al., 2023 ). Alejandro Escánez has been funded by the Action funded by the Ministry of Universities under the application 33.50.460A.752 and by the European Union NextGeneration EU/PRTR through a Margarita Salas contract of the University of Vigo, as well as by the Ministry of Science and Innovation project DeepCom CTM2017‐88686‐P.…”
Section: Acknowledgmentsmentioning
confidence: 99%